2020
DOI: 10.3390/foods9030323
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Jasmonic Acid, Yeast Extract Elicitation, and Drying Methods on the Main Bioactive Compounds and Consumer Quality of Lovage (Levisticum officinale Koch)

Abstract: The aim of the study was to evaluate changes in the activities of some enzymes (polyphenol oxidase—PPO and peroxidase—POD), the content of some bioactive compounds, and the organoleptic quality and color parameters of fresh lovage and its herb dried with various methods and elicited with jasmonic acid (JA) and yeast extract (YE). Elicitation only slightly affected the sensory quality of the fresh herbs, but consumer responses in terms of acceptability of the dried lovage color showed that lovage from microwave… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 32 publications
0
14
0
Order By: Relevance
“…Previous research indicated that drying caused significant losses of some bioactive compounds, e.g., vitamin C and plant pigments (carotenoids and chlorophylls). Additionally, it should be noted that phenolic compounds that were present in elicited and control lovage leaves turned out to be the least sensitive to degradation during the drying process [ 9 ]. Therefore, this group of bioactive compounds will determine the health-enhancing properties of dried lovage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research indicated that drying caused significant losses of some bioactive compounds, e.g., vitamin C and plant pigments (carotenoids and chlorophylls). Additionally, it should be noted that phenolic compounds that were present in elicited and control lovage leaves turned out to be the least sensitive to degradation during the drying process [ 9 ]. Therefore, this group of bioactive compounds will determine the health-enhancing properties of dried lovage.…”
Section: Discussionmentioning
confidence: 99%
“…Fresh herbs were dried using four techniques: natural (traditional) drying (in a darkened room, a temperature of 20 °C to 22 °C, for approximately seven days), convection drying (in a drying oven at 40 °C for approximately 5 h), microwave drying (in a laboratory microwave dryer, microwave power 360 W at 20 °C, for ca. 5 min), and freeze-drying (in a lyophilizer at a temperature of −49 °C and pressure of 0.045 mbar) [ 8 , 9 ].…”
Section: Methodsmentioning
confidence: 99%
“…Soon after, Naves (1943) discovered and characterized four phtalides (butyl phtalide, butyl dihydrophtalide, butyl tetrahydrophtalide, and butylidene phthalide) [ 4 ]. Subsequently, approximately 20 representatives of the phtalides group were isolated from the plant [ 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 ] ( Table 1 ). Further investigation led to detection of polyynes, mono- and sesquiterpenes, phenolics, and other groups [ 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the presence of some simple phenols (eugenol, carvacrol, methyl salicylate, cuminaldehyde, estragole, and pentyl benzene) is known in volatile extracts of roots [ 4 , 11 , 21 ], fruits [ 6 , 25 ], and leaves [ 21 ], and the presence of hydroxycinnamates (derivatives of caffeic acid, ferulic acid, etc.) [ 10 , 12 , 14 , 15 , 29 , 30 , 31 ], coumarins [ 4 , 14 , 15 , 28 ], and flavonoids [ 12 , 14 , 15 , 29 ] is known in alcohol-derived extracts of the roots and leaves. Trustworthy information regarding fresh lovage roots is extremely scarce, partially owing to the difficulties of practical work with fresh tissue.…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, food is considered as a source of not only dietary compounds but also biologically active compounds that may exert a beneficial effect on human health and condition of the organism. The growing consumers’ awareness of the impact of diet on health is reflected in their choice of raw products rich in vitamins, minerals, and other bioactive compounds such as polyphenols [ 1 ], anthocyanins [ 2 ], carotenoids [ 3 , 4 ], essential oils [ 5 ], or peptides [ 6 ].…”
Section: Introductionmentioning
confidence: 99%